The Mother's Role in Building Children's Intelligence Using Social Media - Musofiana, Ida; Madrah, Muna Yastuti; Laksana, Andri Winjaya (International Journal of Law Society Services, 2023)
Social media is a collection of internet-based applications based on web 2.0 ideology and technology to enable the creation and exchange of content by its users. The impacts arising from the covid-19 pandemic have affected all aspects, including legal, social, educational, etc. Like online schools, children often use cell phones to teach and understand that cell phones used to use social media should be intelligent and wise. This study uses sociological juridical research methods by going directly to the field to determine the actual conditions. This study indicates that mothers have difficulty understanding the importance of being intelligent and wise in using social media because if they are not wise and intelligent, it can cause new problems, not only social problems but also legal problems. The government has issued Law concerning Electronic Information and Transactions. It regulates various things to protect against the misuse of electronic information flows.